The Christian Faith: Creed in the Indian Context - Puthumattathil, Shinto (Asian Horizons, 2011)
Ignatius Puthiadam and Xavier Irudayaraj, The Christian Faith: Creed in the Indian Context, Bangalore: Asian Trading Corporation, 2008, Pages 297, ISBN: 817086459-3